2018
DOI: 10.1111/fcp.12352
|View full text |Cite
|
Sign up to set email alerts
|

Imoxin attenuates high fructose‐induced oxidative stress and apoptosis in renal epithelial cells via downregulation of protein kinase R pathway

Abstract: Double-stranded RNA (dsRNA)-activated protein kinase R (PKR), a ubiquitously expressed serine/threonine kinase, is a key inducer of inflammation, insulin resistance, and glucose homeostasis in obesity. Recent studies have demonstrated that PKR can respond to metabolic stress in mice as well as in humans. However, the underlying molecular mechanism is not fully understood. The aim of this study was to examine the effect of high fructose (HF) in cultured renal tubular epithelial cells (NRK-52E) derived from rat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…However, no studies have been done so far to explore the role of PKR in hypertension related renal damage. Previously, we have reported the association of PKR in endothelial dysfunction, cardiovascular remodeling and renal inflammation [18,19]. In continuation with our previous study, we establish the role of PKR in NG-Nitro-L-arginine Methyl Ester, Hydrochloride (L-NAME) induced renal damage.…”
Section: Introductionsupporting
confidence: 83%
“…However, no studies have been done so far to explore the role of PKR in hypertension related renal damage. Previously, we have reported the association of PKR in endothelial dysfunction, cardiovascular remodeling and renal inflammation [18,19]. In continuation with our previous study, we establish the role of PKR in NG-Nitro-L-arginine Methyl Ester, Hydrochloride (L-NAME) induced renal damage.…”
Section: Introductionsupporting
confidence: 83%
“…PKR is known to mediate the antiviral effects of interferons in leukocytes, regulate cell inflammation, proliferation and apoptosis in uninfected cell types and may thus be involved in a variety of CVD associated with chronic inflammation. 19,23,26 Previous studies have shown SFAs induce apoptosis in many cell types and is associated with the development of metabolic disorders, such as diabetes, hypertension and heart disease. 4,[28][29][30][31][32][33][34][35][36] To know whether PKR inhibition prevents PA-induced apoptosis, we determined apoptosis by FACS analysis (Figure 2A and 2B) and caspase-3 expression (Figure 2C and 2D), we observed the inhibition of PKR could prevent apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Cells were incubated for 24 hours with different treatments and harvested under 4‐8°C conditions. Apoptosis assay was performed using Annexin V/PI apoptosis kit by flow cytometry as mentioned previously …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clearly, it could be hypothesized that specific pharmacological inhibitors against particular RNA-RBPs would restore normal insulin signaling, glucose and lipid metabolism, and ameliorate inflammation and fibrosis of metabolic tissues, such as is observed in obesity-induced steatohepatitis. As a proof of principle, small chemical inhibitors were tested to block the activity of PKR, such as imoxin and 2-aminopurine (199, 200), and when used under immune-metabolic stress conditions resulted in improvements in immune-metabolic phenotypes in a mouse model (156). Additionally, new chemical agents are being developed that antagonize the miRNA-Ago2 protein complex, including anti-miRNA–Ago2 and tiny locked nucleic acids (LNAs), by binding to the active site of Ago2 protein and seed region of miRNAs, thereby resulting in functional inhibition of Ago2-mediated miRNAs (201203).…”
Section: Introductionmentioning
confidence: 99%